A four country comparison of spite, cooperation and errors in voluntary contribution mechanisms - Jordi Brandts; Tatsuyoshi Saijo; Arthur Schram (Osaka University, Institute of Social and Economic Research (ISER), 2000)
This paper presents data from experiments with a linear voluntary contributions mechanism for public goods conducted in Japan, the Netherlands, Spain and the USA. The same experimental design was used in the four countries. Our 'contribution function' design allows us to obtain a more complete picture of subjects' behavior than previous studies; it yields information about situations where it is a dominant strategy to contribute all the endowment and about situations where it is a dominant strategy to contribute nothing. Our results show, first, that differences in behavior across countries are not large. Second, the evidence for spiteful behavior by Japanese subjects, that has been observed in other studies, is not confirmed by our results. Third, as a whole our data are inconsistent with the explanation that subjects contribute only out of confusion.
Keywords: 330; Verhaltensökonomik; Öffentliche Güter; Test; Spieltheorie; Vergleich; Theorie; Japan; Niederlande; Spanien; USA